The rule of recognition and the U.S. Constitution - Adler, Matthew D.; Himma, Kenneth Einar (New York ; Oxford : Oxford University Press, 2009)
This volume includes both jurisprudence, using the U.S. as a 'test case' that highlights the strengths and limitations of the rule of recognition model, and constitutional theory, by showing how the model can illuminate topics such as the role of the Supreme Court, the constitutional status of precedent, and much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Constitutional law -- United States -- Philosophy; Jurisprudence -- United States -- Methodology; Legal positivism; Hart, H. L. A. -- 1907-1992.